Analisis Kesiapan Guru Dalam Melaksanakan Sistem Pembelajaran Pada Kurikulum Merdeka Di UPT SD Negeri 40 Gresik - Ishlahiyah Afhami; Ismail Murzaki (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine the readiness of elementary school teachers in implementing the independent curriculum. This type of research is descriptive qualitative. The subjects in this research were grade 1 and grade 4 teachers at UPT SD Negeri 40. The instruments used were interview guides and documentation. The data analysis used in this research is qualitative data analysis, namely summarizing the results of the interview data that have been described. The results of this research indicate that teachers are well prepared to create lesson plans for an independent curriculum for grade 1 and grade 4 educators, which have been renamed teaching modules. To ensure that these teachers can implement these modules effectively, they are trained through online and offline methods to observe, research, and adapt teaching modules from various sources. In preparation for implementing the independent curriculum, teachers in both first and fourth grade are committed to learning together in the KKG community. This involves collaborating with peers in groups to develop teaching modules, structure ATPs, and set learning objectives. In this way, teachers in grades 1 and 4 demonstrate their readiness to implement effective and impactful learning in their classes and teachers' readiness to evaluate learning in an independent curriculum is demonstrated with a systematic approach. First, the teacher identifies each student's learning abilities. After that, the assessment tool. developed to facilitate evaluation. Beyond traditional evaluation methods, Project-based learning evaluations are also incorporated to reflect students' Pancasila profiles, usually referred to as P5 projects.